Analysis of two-dimensional hydrodynamic flows on tropic slope surfaces - Rodríguez-Poltronieri, Ronald Andrés (2023)
Few studies reflect the hydrodynamic behavior of surface flows on slopes of the tropics, despite the number of modeling tools currently available. The present investigation is a contribution that helps to increase the knowledge of the dynamics of the runoff on the slopes, as an extra study of the behavior of the precipitations on these. The analyzes carried out take relevance within the basic studies of a project, developing within the disciplines of hydrodynamics, geology and environment. The case studied is found on a slope in the Cervantes sector, which has already been intervened with a double-reinforced steel mesh as a superficial erosive control. With the research, a comparison of applied works and a new sustainable proposal are made using bidimensional modeling tools. The models reflect the behavior of the flow velocities in general and specific due to the distribution on a slope, a comparison of their flow velocities was made in three scenarios, having a decrease of 33.73% to 48.88% in the flow velocities of the proposed coverage, both for events with a return period of 50 and 100 years. In addition, a climate change effect was analyzed, which verified that the flow speeds do not exceed the theoretical drag limits for the proposed model and in which case it was fully complied with. As runoff control, the proposed coverage fulfills its function. However, due to the particular conditions of the analized slope, the proposal works as a complement to the applied measures.